Chernobyl explosion : how a deadly nuclear accident frightened the world - Burgan, Michael (Captured history. Science., 2018)
Examines the deadly explosion at Chernobyl and the lasting effects of the disaster. Includes a map, a timeline, a glossary, resources for further information, as well as archival and color photographs.